Knowledge and awareness in psychodermatology: Findings from a survey among Ibero-Latin American dermatologists - Julio Torales; Iván Barrios; Alejandra Echagüe; Ximena Paredes; Anthon Torres-Romero; Karina Malvido; María Alejandra Vázquez; Marcelo O’Higgins; Tomás Caycho-Rodríguez; Mohammad Jafferany; João Mauricio Castaldelli-Maia; Antonio Ventriglio (Industrial Psychiatry Journal)
Background: Psychodermatology is an interdisciplinary field that bridges psychiatry and dermatology, addressing the psychosocial and psychiatric aspects of skin diseases. Managing such cases presents a challenge for both dermatologists and psychiatrists as patients often resist psychiatric consultations, complicating diagnosis and treatment. Aim: This study aimed to assess the level of knowledge and awareness of psychodermatology among dermatologists in Ibero-Latin America, explore their experiences with psychodermatological conditions, and identify the educational needs and challenges in this interdisciplinary field. Materials and Methods: An observational, descriptive, cross-sectional study was conducted through an online survey from December 2023 to March 2024. The survey was distributed through messaging apps and emails and targeted a sample of dermatologists from Ibero-Latin America to explore their experience, training, and perceived challenges in psychodermatology. The participants were selected through non-probabilistic sampling from the staffing records of the Ibero-Latin American College of Dermatology. Results: Of 301 dermatologists, the vast majority (99%) reported a good level of knowledge in the field of psychodermatology; however, only 36.5% had substantial clinical experience with these conditions. Approximately 70.1% did not prescribe psychotropic medications, reflecting hesitancy or lack of confidence in managing the psychiatric issues of dermatological conditions. The study also highlighted a strong preference (86.7%) for a multidisciplinary approach for managing psychodermatological disorders. Significant perceived challenges included limited access to professional training and patients’ reluctance to accept psychological contributions to their dermatological conditions. Conclusion: The level of knowledge in psychodermatology is widespread among Ibero-Latin American dermatologists, even though a significant gap in practical experience and confidence in integrating psychological management into their dermatological practice was found. These findings emphasize the need for enhanced professional training programs and an interdisciplinary approach to effectively address psychodermatological conditions.